Triaging and referring in adjacent general and emergency departments (the TRIAGE-trial): A process evaluation of medical staff experiences in a nurse-led triage system. (July 2022) - Meysman, Jasmine; Morreel, Stefan; Lefevere, Eva; Verhoeven, Veronique; De Graeve, Diana; Monsieurs, Koenraad G.; Philips, Hilde
Highlights: A grounded theory study identified facilitators and inhibitors in the implementation of nurse-led triage. ED Triage with streaming to GPs lowererd perceived workload for the ED. An extended triage protocol increased complexity and triage time. Experience and personal characteristics of ED nurses determined confidence in the protocol. Communication training and feedback can facilitate the implementation process. Abstract: Aims: This process evaluation aims at identifying the facilitators and inhibitors that influenced the successful uptake of a nurse-led triage system streaming low-risk patients from an emergency department (ED) to the general practitioner (GP). Design & Methods: Semi-structured interviews with ED nurses (n = 12), ED doctors (n = 6) from the ED of a Belgian general hospital and GPs (n = 5) affiliated with the adjacent GP cooperative (GPC). The process evaluation ran in parallel with the TRIAGE trial that started in March 2019 and ended 31st of December 2019. The first set of interviews was conducted in June 2019 and the second set in January 2020. Data were analysed based on grounded theory. Results: Through a deductive framework, facilitators and inhibitors could be identified on three levels: the organisational, group and individual level. Main inhibitors are the degree of risk aversion of individual nurses, possible language barriers during delivery of the triage advice and the non-adapted ED infrastructure. Training on both the use of the triage protocol and effective delivery of the triage advice, in combination with periodical feedback from the GPC were the most important facilitators. Conclusion: Based on the process evaluation we can conclude that a consensus exists among stakeholders that the ED Nurses are considered ideally positioned to perform the triage of walk-in patients, although a certain degree of experience is necessary. Although the extended triage protocol and GPC referral increases the complexity and duration of triage and entails a higher workload for the triage nurses, ED nurses found it did lead to a lower (perceived) workload for the ED in general.